The Performance of Small-Town Water Systems in the Upper West Region of Ghana - Bowan, Patrick Aaniamenga; Amin, Adams Duma (European Scientific Journal, ESJ, 2026)
Small-town water systems are water supply systems built primarily for people living in rural or peri-urban areas in many developing countries. This study examined the performance of small-town water systems in the Upper West Region (UWR) of Ghana, focusing on functionality, management practices, and sustainability challenges. The study adopted an exploratory research design and applied both qualitative and quantitative methods, using surveys and interviews with water users, system operators, and officials from the Community Water and Sanitation Agency (CWSA). The findings revealed that while most assessed small-town water systems were functional, they operated below optimal levels, with overall coverage below 3% across all selected districts. Frequent pump failures (46%), pipe leakages (22%), and an unstable power supply (16%) were identified as the main technical problems. Over half of the system operators lacked adequate training, and community involvement in managing the water systems was rare, as management was overly centralised under the CWSA. The study recommends the adoption of solar-powered mechanised water systems to reduce power-related interruptions, and a holistic approach to the management of the water systems that integrates technical efficiency, financial accountability, strong institutional collaboration, and inclusive community ownership to ensure the sustainability and optimal performance of small-town water systems in the UWR and similar systems in other developing countries.